2009
DOI: 10.1002/jmv.21388
|View full text |Cite
|
Sign up to set email alerts
|

Infection of B cells with hepatitis C virus for the development of lymphoproliferative disorders in patients with chronic hepatitis C

Abstract: Infection with hepatitis C virus (HCV) is associated with lymphoproliferative disorders, represented by essential mixed cryoglobulinemia and B-cell non-Hodgkin's lymphoma, but the pathogenic mechanism remains obscure. HCV may infect B cells or interact with their cell surface receptors, and induce lymphoproliferation. The influence of HCV infection of B cells on the development of lymphoproliferative disorders was evaluated in 75 patients with persistent HCV infection. HCV infection was more prevalent (63% vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 37 publications
2
48
0
Order By: Relevance
“…This basic issue, however, has not yet been definitively settled. Thus, although HCV has been detected in lymphocytes from HCVinfected patients 59,60 and patients with MC, 61 only in a minority of cases also RNA-negative strands, ie, the HCV replicative intermediates suggestive of viral replication, were detected in the cells. 59 Detection of RNA-negative strands by polymerase chain reaction, however, may give rise to false-positive results.…”
Section: Evidence For An Oncogenic Role Of Hcv In Nhlmentioning
confidence: 94%
See 1 more Smart Citation
“…This basic issue, however, has not yet been definitively settled. Thus, although HCV has been detected in lymphocytes from HCVinfected patients 59,60 and patients with MC, 61 only in a minority of cases also RNA-negative strands, ie, the HCV replicative intermediates suggestive of viral replication, were detected in the cells. 59 Detection of RNA-negative strands by polymerase chain reaction, however, may give rise to false-positive results.…”
Section: Evidence For An Oncogenic Role Of Hcv In Nhlmentioning
confidence: 94%
“…Thus, although HCV has been detected in lymphocytes from HCVinfected patients 59,60 and patients with MC, 61 only in a minority of cases also RNA-negative strands, ie, the HCV replicative intermediates suggestive of viral replication, were detected in the cells. 59 Detection of RNA-negative strands by polymerase chain reaction, however, may give rise to false-positive results. 62,63 More recently, Marukian et al 64 have shown that culture-grown HCV replicated in hepatoma cells, but no HCV replication was detected in B or T cells, monocytes, macrophages, or dendritic cells from healthy donors.…”
mentioning
confidence: 99%
“…Notably, mutations in TP53, CTNNB1, and BCL6 were also identified in peripheral blood mononuclear cells (PBMC) of HCV-positive patients (12), although only about 10% of PBMC are B cells. As TP53 is a tumor suppressor gene and BCL6 and CTNNB1 are protooncogenes, mutations in these genes might be of pathogenetic relevance.Regarding the reported mutagenic effect of HCV, it should be mentioned that it is still controversially discussed whether HCV indeed infects B cells and induces mutations by a hit-and-run mechanism, or whether the effects seen are due to the binding of HCV to costimulatory receptors expressed on the surface of B cells, such as CD81 (17)(18)(19)(20)(21)(22)(23)(24).In the present work, we aimed to clarify whether the mutagenic effect of HCV on TP53, CTNNB1, and BCL6 is detectable in B cells of chronically HCV-infected patients, and hence might represent a main factor for B-cell lymphoproliferative diseases in such patients. …”
mentioning
confidence: 99%
“…High levels of RF are frequently observed not only in patients with rheumatic diseases, but also with nonrheumatic diseases, including mixed cryoglobulinemia, Sjögren s syndrome, mixed connective tissue disease, and even in healthy subjects 11 . We have previously reported a small-scale study that found 48 and 41 of patients with CH-C and CH-B, respectively, had abnormally high levels of RF 3 . Another group has also reported that RF abnormalities are observed in 4 of healthy subjects 12 .…”
Section: Discussionmentioning
confidence: 94%
“…But this reference value has been changed to less than 15 IU/mL in Japan recently. In our previous study, investigating abnormalities of LPD markers in patients with CH-C, we regarded patients with an RF of more than 10 IU/mL as having a high level 3 . Therefore, in this study we also regarded patients with CH-B whose RF was more than 10 IU/mL to have high levels of RF.…”
Section: Discussionmentioning
confidence: 99%